111 Out of hours support: a review of the 24 hour advice line for south east wales from marie curie hospice cardiff and the vale. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Lewis, Heledd; Hayes, Joanne; Osborn, Hannah
Abstract : Introduction: The Marie Curie Hospice, Cardiff and the Vale runs a twenty four hour specialist palliative care telephone advice service for patients, relatives and other health care professionals. It supports a seven days a week clinical nurse specialist (CNS) palliative care service in all settings across South East Wales. Calls are handled by hospice in patient nurses. Calls from healthcare professionals are passed onto the appropriate specialist palliative care team which consists of a CNS team and on call specialty trainees or consultants in palliative medicine. Calls from patients and relatives are either dealt with by the inpatient nurses, passed onto the appropriate specialist palliative care team or GP out of hours. Method: A Retrospective review of advice calls received at the hospice between 1st April-20th September 2018. Results: There were 336 calls to the advice line in the 6 month period, a mean of 56 calls per month. Of these 34% were previously known to Marie Curie. 74% of the calls were from the patient's own home. The duration of advice calls to the inpatient nursing staff amounted 46.2 hours. 53% of the calls were over the weekend and 27% of calls were passed onto the oncall Doctor. 17% of the calls were passed onto the CNS. Of the callers to the advice line 36% were relatives and 21% were other doctors (GP or junior doctor) calling for advice. The majority of calls to the advice line were regarding symptom control, patient advice or medication queries. Conclusion: As demonstrated, the advice line is a successful means of support for patients, their carers and other health care professionals. The Marie Curie hospice in Cardiff is working collaboratively with other organisations to extend support and advice beyond its usual patient population 24 hours a day seven days a week.